RELEVANSI KRITIK BUDAYA SIRI SEBAGAI MAKNA ESTETIK ETOS KERJA DALAM NOVEL PULAU KARYA ASPAR PATURUSI PADA MASYARAKAT BUGIS-MAKASSAR DI KOTA TERNATE - NFN Wildan (SAWERIGADING, 2011)
Through the novel Pulau, Siri culture with its humanistic values that direct to work ethos growth is reconstructed. This form of reconstruction and solution to current situations through the aesthetics structure of the novel Pulau is without decreasing the values reflected in Siri culture. Through sociological theory of literature, Siri culture as expected to develop the spirit of work ethos correlate positively with economy activities of Bugis-Makassar migrant society in Ternate of North Maluku. The emergence of (the spirit of work ethos is not because of the obligation to save lives, but it is to show prestige through the success of established economy. The aim of this research is to reveal and explain the falshback of aesthetical values content in 'Siri' culture (budaya Siri') viewed from cultural critcs of Bugis-Makassar tribes. In addition, this research is also aimed to offer solutions and function of aesthetical critics in "Pulau", and to reveal relevance and influence of 'Siri' in developing spirit of work of Bugis-Makassar migrant society in Ternate City, especially in economic activities. Qualitative method is used in this research in interpreting aesthetical values comprehensively and presenting the analysis in a descriptive way. Abstrak Melalui novel Pulau, budaya siri dengan nilai humanis mengarah pada pertumbuhan etos kerja yang direkonstruksi. Tanpa mengurangi nilai yang terefleksi dalam budaya siri dalam struktur novel Pulau, bentuk dari rekonstruksi dan solusi bagi situasi ini tetap ada. Melalui teori sosiologi sastra, budaya siri seperti yang terefleksikan dapat mengembangkan spirit etos kerja yang berkorelasi secara positif dengan aktivitas ekonomi masyarakat migran Bugis-Makassar di Ternate, Maluku Utara. Kemunculan spirit etos kerja bukan karena menjaganya tetap hidup, tetapi untuk menunjukkan prestise melalui keberhasilan ekonomi yang dibangun. Tujuan penelitian ini adalah untuk mengungkap dan menjelaskan kilas-balik isi nilai estetik dalam budaya siri yang ditinjau dari kritik budaya suku BugisMakassar. Penelitian ini juga untuk menawarkan solusi dan fungsi kritik estetika dalam novel Pulau dan mengungkap relevansi serta pengaruh siri dalam mengembangkan spirit kerja masyarakat migran Bugis-Makassar di Kota Ternate, khususnya dalam aktivitas ekonomi. Metode kualitatif digunakan dalam penelitian ini untuk menginterpretasi nilai estetika secara komprehensif dan mengemukakan analisis secara deskriptif.